2014
DOI: 10.1002/app.41395
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and gas permeation parameters of metathesis polytricyclononenes with pendant Me3E‐groups (E = C, Si, Ge)

Abstract: Metathesis polytricyclononenes were synthesized via ROMP polymerization in the presence of the 1‐st generation Grubbs catalyst and their gas‐transport properties were studied for the first time. The aim of this work was to evaluate the influence of Me3E‐groups (E = C, Si, Ge) on gas permeation parameters of ROMP materials. New metathesis poly(3‐tert‐butyltricyclononene‐7) and poly(3‐trimethylgermyltricyclononene‐7) were obtained with high yields (up to 95%) and high‐molecular weights (Mw∼3–7×105 g mol−1). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…So both of these polymers have similar decomposition temperatures and it seems that the main contribution to the thermal behavior is attributed to the tricyclononene monomer unit structure. This assumption is consistent with previously obtained results for other metathesis polytricyclononenes . A somewhat higher stability of these polymers was observed in the inert atmosphere for both polymers due to minimization of double bond oxidation processes during the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So both of these polymers have similar decomposition temperatures and it seems that the main contribution to the thermal behavior is attributed to the tricyclononene monomer unit structure. This assumption is consistent with previously obtained results for other metathesis polytricyclononenes . A somewhat higher stability of these polymers was observed in the inert atmosphere for both polymers due to minimization of double bond oxidation processes during the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that addition type polynorbornenes are more permeable than metathesis polymers but the latter are more readily obtained due to the high driving force of metathesis polymerization of high strain norbornene monomers . High gas permeability level of these polymers was caused by the presence of spherical bulky groups (e.g., trimethylsilyl groups or trimethylgermyl groups) and rigid polymer chains which disrupt a dense polymer chain package . Bulky SiMe 3 groups were also introduced into other classes of polymers (polyacetylenes, polystyrenes, polysulfones, poly(phenylene oxide), polyolefins).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norbornene and its derivatives are an unusual class of monomers that can be polymerized by various mechanisms forming polymers with different structures of main chains and properties . This feature, along with the ability to synthesize series of norbornenes with a regularly varying structure, has made these compounds attractive for the macromolecular design of polymers with desired properties and for the systematic study of the relationships “polymer structure‐properties.” Depending on the nature of the side substituents and the structure of the main chain, norbornene‐based polymers can have attractive optical properties, low moisture absorption, thermal and chemical stabilities, promising membrane characteristics, etc. Dicyclopentadiene (DCPD) is one of the most readily available norbornene derivatives, which is obtained by dimerization of cyclopentadiene—a component of light fraction of oil pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This high permeability is attributed to high gas diffusivity, which is caused by having a trimethyl silyl group as bulky side chain. Numerous studies focus on polymer materials that possess pendant groups as side chains to improve gas permeability because the pendant groups be able to restrict mobility and molecular rotation of polymer main chain …”
Section: Introductionmentioning
confidence: 99%